2019
DOI: 10.5863/1551-6776-24.3.234
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of Antipsychotic Medications Administered to Psychiatric Patients in a Tertiary Care Pediatric Emergency Department

Abstract: OBJECTIVES An increasing number of pediatric patients with psychiatric chief complaints present to emergency departments (EDs) nationwide. Many of these patients require treatment with antipsychotic medications to treat agitation. We sought to examine the use of antipsychotic medications in pediatric patients presenting to a tertiary care pediatric ED. METHODS We performed a retrospective electronic medical record review of patients presenting to a tertiary care pediatric hospital from January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The literature on the use of psychiatric medications with children and youth in ED settings is quite sparse. Rudolf et al ( 2019 ) identified 224 youth who received antipsychotic medications in the pediatric ED of a tertiary care hospital between 2009 and 2016. Chief complaints were suicidal ideation (47.6%), aggression (28.0%), homicidal ideation (10.5%), hallucinations (7.4%), and agitation (6.1%).…”
Section: Categories Of Informationmentioning
confidence: 99%
“…The literature on the use of psychiatric medications with children and youth in ED settings is quite sparse. Rudolf et al ( 2019 ) identified 224 youth who received antipsychotic medications in the pediatric ED of a tertiary care hospital between 2009 and 2016. Chief complaints were suicidal ideation (47.6%), aggression (28.0%), homicidal ideation (10.5%), hallucinations (7.4%), and agitation (6.1%).…”
Section: Categories Of Informationmentioning
confidence: 99%
“…Similarly, Rudolf et al reported a comparable atypical antipsychotic use (olanzapine, 51.1%; aripiprazole, 26.6%) among PED psychiatric patients. 27 Predictors of acute agitation reported in prior studies include a history of disruptive behavior, autism spectrum disorder and intellectual disability, ADHD, psychosis, substance intoxication or withdrawal, and disruptive, impulse control, and conduct disorders. 4,19,32,34 Independent predictors of agitation and restraint use observed in this study were consistent with the observed predictors in prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in keeping with prior reports, our study establishes that restraint use was independently associated with longer ED LOS and higher admission rates. 27,32 Prior studies have suggested that restraint use may be an indicator of more severe disease state, leading to higher admission rates. 32 In conclusion, acute agitation remains a relatively common behavioral health emergency seen in the ED.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations